PENGUASAAN KONSEP FISIKA SISWA KELAS XI SMAN 1 KEPENUHAN MELALUI PENERAPAN MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE AND SHARE) - Siti Hardianti Arimi; Azizahwati Azizahwati; M. Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Concept mastery is the ability of students to understand science scientifically both concepts in theory and their application in everyday life. The SSCS learning model is able to improve students' concept mastery abilities. The method used to measure the level of mastery of student concepts is done by applying Bloom's taxonomy to the categories of remembering, understanding, applying, analyzing, evaluating, and creating. The research method used in this study is a quasi-experimental design with Posttest-Only Design. The sample chosen by simple random sampling technique was class XI IPA 2 as an experimental class totaling 34 students and class XI IPA 3 as a control class with a total of 33 students. The research instrument used the ability to test the mastery of physics concepts based on Bloom indicators in the C1 to C6 question categories.Data collection techniques in the form of scores on the mastery of students' physics concepts after the learning process was carried out in both classes. Data were analyzed descriptively by looking at student score results and analyzed inferentially usingthe independent sample t-test. The results showed the average physics concept mastery score of students who studied with the SSCS model was higher than conventional learning. Learning by applying the SSCS model gives a good influence, activities and cooperation of students increases and makes students more enthusiastic in learning so as to increase mastery of the concept of class XI students of SMAN 1 Kepenuhan on the material Elasticity and Hooke's Law.Key Words:SSCS, Mastery of Concepts, Elasticity and Hooke's Law